VD_FINDINFO Décision / 2020 / 172 vom 3. März 2020 - VD Tribunal cantonal (2020)
RÉCUSATION, DILIGENCE, INDÉPENDANCE DE L'AVOCAT, CONFLIT D'INTÉRÊTS | 12 let. a LLCA, 12 let. b LLCA, 12 let. c LLCA, 56 let. f CPP (CH)